Metastatic Leiomyosarcoma Involving Bone and Kidney in an Adult Budgerigar ( Melopsittacus undulatus ) - Hemad Shafiei; Reza Kheirandish; Hamzeh Soltani; Ali Keshavarzrad; Shahriar Dabiri (Veterinary Medicine and Science, 2026)
ABSTRACT Leiomyosarcoma (LMS), a malignant neoplasm of smooth muscle cell origin, is relatively rare in birds. This study presents the occurrence of this tumour in a 2‐year‐old male budgerigar. The bird was brought to the Ashian Veterinary Hospital with complaints of swelling in the medial area of the left leg. Clinical examination and radiological imaging confirmed the presence of soft tissue swelling in the medial region of the left leg. Empirical antibiotic and anti‐inflammatory therapy were used to distinguish infectious inflammation from the tumour mass. After 12 days, a clinical diagnosis of suspected neoplasm was made due to a lack of improvement and increasing mass size. Given the deterioration of the bird's general condition, euthanasia was recommended and performed. At necropsy, all viscera were biopsied for histopathological evaluation. Microscopic examinations confirmed the initial diagnosis of LMS. To confirm the diagnosis, immunohistochemical staining was performed using antibodies to alpha‐smooth muscle actin (α‐SMA), vimentin and desmin. The results of α‐SMA and desmin staining definitively confirmed the presence of an LMS neoplasm with metastasis to the bone and kidneys; however, vimentin staining was negative.